Pr??ticas da experi??ncia e do relacionamento nas abordagens da cocria????o de valor e teoria dos stakeholders: um estudo de casos multiplos em academias de gin??stica em S??o Paulo capital - Tavares, Vanessa Carvalho Miranda (2016)
The value cocreation suggests organizations take their focus from product and service giving customer space. Currently, there is a change in behavior and attitude of customers who come from a passive position to a connected and informed manner, requiring an adaptation of organizations to this new attitude of customers. Organizations of several areas aim to provide unique experiences to their customers and thereby achieve a more effective relationship with stakeholders resulting in mutual benefits. With the growing positioning of the sports industry and the adequacy of physical activity practices to the modern world, the gyms market is growing, turning an interesting object of study. The aim was to analyze how the practices of existing experience and relationships in the value cocreation approaches and theory of stakeholders were present in gyms and how they impact the management of these organizations. The methodology applied was the multiple cases study in the gyms, for data collection, we used sources of evidence for the triangulation of data as proposed by Yin (2010): observation, document analysis and scripts for semi-structured interviews. The results showed that teachers are important stakeholders for the development of the relationship and providers of memorable experiences to the other stakeholders. It is concluded that the gyms practice the value cocreation partially with their stakeholders and unconsciously because they have no knowledge of theory to practice.